Epoxy-functional diblock copolymer spheres, worms and vesicles via polymerization-induced self-assembly in mineral oil. Issue 19 (29th April 2020) - Docherty, Philip J.; Girou, Chloé; Derry, Matthew J.; Armes, Steven P.
Abstract : Epoxy-functional poly(stearyl methacrylate)-poly(glycidyl methacrylate) spheres, worms or vesicles can be prepared by RAFT dispersion polymerization of glycidyl methacrylate in mineral oil at 70 °C. Abstract : Epoxy-functional diblock copolymer spheres, worms and vesicles are synthesized at 30% w/w solids via reversible addition–fragmentation chain transfer (RAFT) dispersion polymerization of glycidyl methacrylate (GlyMA) in mineral oil at 70 °C. This is achieved by using a relatively short oil-soluble poly(stearyl methacrylate) (PSMA) macromolecular chain transfer agent (macro-CTA) with a mean degree of polymerization of 9. Gel permeation chromatography (GPC) studies indicate that good control over the molecular weight distribution can be obtained and the resulting PSMA9 -PGlyMA x nano-objects are characterized by dynamic light scattering (DLS), transmission electron microscopy (TEM) and small-angle X-ray scattering (SAXS). Oscillatory rheology studies of a 30% w/w PSMA9 -PGlyMA75 worm gel indicate that thermally-triggered degelation occurs on heating to 100 °C. TEM studies indicate that a partial worm-to-vesicle transition occurs under such conditions.